Saratov village during the Great Patriotic War: The mobilization policy of the state and the practice of survival - Danilov, Victor N. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2022)
The article examines the state of agriculture and the financial situation of rural residents of the Saratov region during the Great Patriotic War from the point of view of the mobilization model of the Soviet economy. The specific indicators and ways of implementing the state policy in the region to maximize the mobilization of human, logistical, food and financial resources of the village in the interests of the army, the impact of this factor on the livelihoods of the population are analyzed. It is concluded that the mobilization policy in the absence of compensatory measures and the deportation of German collective farmers led to an extreme weakening of the productive forces of the collective farm village of the region. In the conditions of war, personal subsidiary farming became not only the main reserve for the survival of the rural population, but also turned out to be an important mobilization resource.